CPW-Fed Penta Band Monopole Antenna for Multiservice Wireless Applications - Kumar, Raj; Kamatham, Yedukondalu; Peddakrishna, Samineni; Gaddam, Ajitha (Advances in Technology Innovation, 2021)
A compact triple T-shaped stub with meander loaded strip antenna for penta band applications is proposed. The rectangular patch antenna with meandered and open-ended slot cuts is utilized to realize four operating bands at 2.45 GHz, 3.1 GHz, 5.3 GHz, and 6.5 GHz with an impedance bandwidth of 400 MHz (2.15-2.550 GHz), 1000 MHz (2.7-3.7 GHz), 200 MHz (5.4-5.6 GHz), and 200 MHz (6.4-6.6 GHz), respectively. For an additional resonance frequency, the length of the central T-shaped stub is slightly modified which causes the variation in the current distribution. As a result, the resonance frequency of 5.5 GHz is divided into two resonance frequency bands which are operating at 5.25 GHz and 5.85 GHz with an impedance bandwidth of 100 MHz (5.25-5.35 GHz) and 200 MHz (5.75-5.95 GHz), respectively. Furthermore, a parametric reflection coefficient and surface current distribution analysis is carried out to understand the strip and slot behavior at resonance frequency bands. Finally, a prototype is fabricated and its reflection coefficient, gain, and radiation pattern are measured. The experimental result shows that the proposed antenna is reliable for penta band applications.